2022
DOI: 10.1007/s11042-022-12900-5
|View full text |Cite
|
Sign up to set email alerts
|

Privacy-preserving federated learning for scalable and high data quality computational-intelligence-as-a-service in Society 5.0

Abstract: Training supervised machine learning models like deep learning requires high-quality labelled datasets that contain enough samples from various categories and specific cases. The Data as a Service (DaaS) can provide this high-quality data for training efficient machine learning models. However, the issue of privacy can minimize the participation of the data owners in DaaS provision. In this paper, a blockchain-based decentralized federated learning framework for secure, scalable, and privacy-preserving computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The machine learning algorithms that can be used in FL include neural networks, which were used in the current study, logistic regression, and a tree-based model ( 19 , 20 ), which is suitable for complex iterative computing scenarios of big data modeling and predictive analysis. The technical characteristics of FL include the following: (I) the data of all parties shall be kept locally without disclosing privacy or violating laws and regulations; (II) under the FL system, each participant has the same identity and status; (III) the modeling effect of FL is the same as that of modeling the whole dataset in 1 place, or there is little difference; and (IV) all participants combine data to establish a virtual common model and a system for mutual benefit ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The machine learning algorithms that can be used in FL include neural networks, which were used in the current study, logistic regression, and a tree-based model ( 19 , 20 ), which is suitable for complex iterative computing scenarios of big data modeling and predictive analysis. The technical characteristics of FL include the following: (I) the data of all parties shall be kept locally without disclosing privacy or violating laws and regulations; (II) under the FL system, each participant has the same identity and status; (III) the modeling effect of FL is the same as that of modeling the whole dataset in 1 place, or there is little difference; and (IV) all participants combine data to establish a virtual common model and a system for mutual benefit ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Query-based pricing is also considered from a privacy perspective [ 55 ]. With the development of big data technology, this class also includes artificial intelligence-related approaches, such as federated learning [ 56 ], deep learning [ 57 ], and other approaches to data pricing. Additionally, there are online pricing platforms [ 58 ], dynamic pricing [ 59 ] and other methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These are the current research hotspots in this field. For instance, Peyvandi et al [ 56 ] suggested a distributed federated learning architecture based on blockchain for safe, scalable, and privacy-preserving smart data pricing. The Stackelberg game is Cluster #9, where researchers primarily concentrate on economic pricing theories, including the data market, auction, and data economics.…”
Section: Research Hotspots and Evolutionary Trendsmentioning
confidence: 99%
“…Allocating responsibility and accountability. As machines and AI systems become increasingly autonomous and influential, issues surrounding responsibility and accountability emerge [52][53][54]. Demoethical frameworks must address the challenges of assigning liability when incidents occur involving intelligent systems.…”
Section: Introductionmentioning
confidence: 99%